Women Participation in Entrepreneurial Activities in the Post COVID-19 Pandemic: Empirical Evidence from SMEs Sector - Sazzad Hossain; Md Shamaun Islam; Susmita Kundu; Omar Faruq; Md. Alomgir Hossen (Health Economics and Management Review)
Entrepreneurs contribute to economic development regarding innovation, job creation and income generation. It is also effectively recognized as a fundamental part of economic development and vital in lifting countries from poverty. Women entrepreneurs organize and manage an organization, particularly a business. Women's entrepreneurship has consistently expanded worldwide during the 20th and 21st centuries. Bangladesh will have a big number of young women and productive workers after the COVID-19 epidemic, allowing them to engage in the Small and Medium Enterprises (SME) sector. Women entrepreneurs can help in the elimination of hunger, the reduction of inequities, and the improvement of children's nutrition, health, and school attendance. Also, it has been acknowledged as an important source of economic growth since it creates new jobs and provides society with various solutions to managerial, organizational, and business challenges. Therefore, the purpose of this research was to determine the impact of technological factors, parental support factors, municipal factors, knowledge and skills factors, psychological factors, and financial factors on women's engagement in innovative business development in the context of Bangladesh's SME sector in the post COVID-19 pandemic. This study included both statistical and discussion of the data. Data was collected from over 300 real Bangladeshi ladies using an online purposive sampling approach. To test hypotheses, the data were evaluated using descriptive statistics, collinearity statistics, and other regression analyses. As per study's results, most variables, including administrative, scientific, and familial cooperation, knowledge and skills, psychological, and financial component, has both advantages statistically impressive relationship with women's involvement in the context of the SME area in Bangladesh in the post COVID-19 pandemic. In the post COVID-19 pandemic, everyone from every sector will use the findings to encourage women's participation in entrepreneurial activities in the context of the SME division in Bangladesh.